A wide‐field microscope utilizing two cellphones for health‐care applications. Issue 2 (24th November 2021) - Yu, Zhenfang; Li, Yunfei; Geng, Dongxian; Wu, Pinghui
Abstract: In this report, we report a wide field‐of‐view (FOV) bright field (BF) microscope with compact and portable optical components, mechanically attached to the existing camera unit of the cellphone. A white screen displayed on a cellphone as the illumination source to pump the sample of interest uniformly for the purpose of the reduction in assembly complexity and alignment. It offers a large FOV of 4.36 × 3.27 mm without digital zoom and a spatial resolution of 1.5 μm. Furthermore, we also have demonstrated the potential application for diseases diagnosis and screening by imaging malaria‐infected blood sample and iron deficiency anemia blood sample in resource‐constrained settings where mobile phone infrastructure is already ubiquitous but microscope is notoriously scarce. Abstract : We demonstrate a wide‐field BF cellphone‐based microscope using compact and portable optical components that are mechanically attached to the existing camera unit of the cellphone. The microscope achieves a 1.5 micron spatial resolution and a wide field‐of‐view of 4.36 × 3.27 mm with no image processing. It could be a very powerful tool for global health‐care applications in resource‐limited regions, such as diagnosis and screening for malaria and iron deficiency anemia.